Changes in functional traits and diversity of typical alpine grasslands after a short-term trampling disturbance - Li, Wei; Zheng, Ting Dan; Cheng, Xi Ping; He, Shu Qiang (Frontiers in Ecology and Evolution, 2023)
Alpine grassland ecosystem supports high diversity of terrestrial flora and fauna species. Despite the ecological importance and economic potential of this unique ecosystem type, it experiences increasing anthropogenic disturbances such as trampling, which impose negative impact on the health and integrity of alpine grasslands. Previous studies of trampling impact on alpine vegetation mainly focus on changes in vegetation cover and taxonomic diversity after trampling disturbance, but rarely test community-level responses of alpine vegetation to trampling from a functional trait perspective. Through the lens of vegetation functional traits, the present study evaluates the impacts of simulated trampling on typical alpine grasslands in Shangri-la, China. The results showed that although increased trampling intensity did not always lead to changes in functional diversity across all three experimental sites, characteristics of community-weighted mean trait values had consistently changed towards plant species with shorter height, reduced leaf area and lower leaf dry matter content, and such strong shifts in functional attributes may further affect ecosystem goods and services provided by alpine grasslands. Therefore, a functional trait approach can help us better understand the mechanisms that drive trait changes, function shifts and vegetation stability following anthropogenic disturbances.